Analyzing the use of information technology in guidance and counseling services in Indonesia and Tanzania: A narrative review - Subira Nahemia Kaserero; Muslihati Muslihati; Muhammad Ramli (Jurnal Inovasi dan Teknologi Pembelajaran, 2024)
Abstrak: Karena kemajuan pesat dalam teknologi informasi, konselor sekolah harus memodifikasi layanan bimbingan dan konseling mereka untuk mencerminkan perubahan ini. Sayangnya, sedikit informasi tentang bagaimana konselor menggunakan TI tersedia, terutama di Tanzania dan Indonesia. Penelitian ini bertujuan untuk menganalisis bagaimana kedua negara ini menggunakan teknologi informasi untuk layanan bimbingan dan konseling. 100 artikel internasional dan Nasional telah direview dari tahun 2014 hingga 2024 di Google Scholar, sedangkan 25 artikel telah dipilih menggunakan model PRISMA. Konselor sekolah menggunakan komputer, smartphone, Microsoft Word, PDF, WhatsApp, Zoom, dan Google Meet. Namun, mereka menghadapi kesulitan seperti keterampilan TIK yang tidak memadai, dan kurangnya pelatihan, mereka sering belajar kemampuan digital baru dari rekan kerja mereka. Studi lebih lanjut tentang penggunaan TIK di negara-negara ini diperlukan, seperti halnya penyelidikan upaya pemerintah untuk meningkatkan literasi digital khusus untuk konselor sekolah. Abstract: In light of rapid advancements in information technology, school counselors must modify their guidance and counseling services to reflect these changes. Unfortunately, there is a paucity of information about how counselors use IT, especially in Tanzania and Indonesia. This study aims to analyze how these two countries use information technology for guidance and counseling services. A total of 100 international and national articles have been reviewed from 2014 to 2024 in Google Scholar, while 25 articles have been selected using the PRISMA model. School counselors use computers, smartphones, Microsoft Word, PDFs, WhatsApp, Zoom, and Google Meet. However, they encounter difficulties, such as inadequate ICT skills and lack of training. Consequently, they frequently learn new digital abilities from their work colleagues. Further studies on ICT use in these nations are required, as well as an investigation of government efforts to enhance digital literacy specifically for school counselors.